Relationships reimagined: Expanding on the behaviour of Oscar Parish Home - Brobäck, Simon; Skarby, Martin (My University, 2023)
In the world of architecture, buildings are sometimes thought of in terms of permanence: What is on the drawing is the perfect solution for all eternity. However, that is an ideal not coinciding with reality. The occupants and a building form a complex relationship to each other and are inherently interlinked. Buildings inevitably change because the predictions of the occupants’ behaviours fall short. This reality testifies the need for better understanding of such relationships. Departing from the texts by Stewart Brand in How Buildings Learn, stating the evolution of buildings trough time as: “First we shape our buildings, then they shape us, then we shape them again – ad infinitum. Function reforms form, perpetually” (Brand, 1994, p.3) On this insight, this project set out to employ behaviorology as a tool for understanding the relationship between occupants and building, and, by extension, informing design. By making observations at a very detailed scale through drawing, text and photos, traces of behaviour are picked up that would otherwise have gone unnoticed, integral to the understanding of how architecture has acted and will act over time: its behaviour. Acting as a breeding ground for intervention is a 1930s parish home on Östermalm in Stockholm, resulting in the study of what it currently is and the reimagination of what it could be. Not only following an uncompromising approach of minimal structural impact in updating the circulation of the building, the project is also based on a philosophy by Sam Jacobs (2012), seeing architecture as a continuum of enactment and re-enactment, repetition and details are the key to forming a whole (p.7). Hence, the interventions become of human scale and are actualized as building components: Objects of interaction, the link between the building and its occupants.